Perceived efficiency and local consensus as factors shaping medicinal plant knowledge - Sousa, Daniel Carvalho Pires; Ferreira Júnior, Washington Soares; Santos, Yasmim Antonio Costa dos; Moura, Joelson Moreno Brito de; Albuquerque, Ulysses Paulino (Ethnobiology and Conservation, 2023)
Environmental perception goes through physiological, psychological, and cultural filters and can influ- ence the selection and usage of species. Additionally, sharing cultural information is a crucial social strategy for our species’ survival. From this standpoint, knowledge that aligns with the local context is typically the most widely "expressed" and/or "replicated" by individuals. Building upon this premise, our objective was to investigate whether knowledge about local medicinal plants is influenced by certain adaptive factors, such as perceived efficacy, perceived availability, and perceived frequency of diseases. The study was conducted with 73 individuals from five rural communities in Vale do Catimbau Na- tional Park, Buíque, Pernambuco, Brazil. A free list of medicinal plants and their therapeutic uses was employed. Using these free lists, we employed a salience index to determine consensus within the local diversity. We employed a generalized linear model with a binomial distribution to ascertain whether perceived efficacy, perceived availability, and perceived disease frequency account for the local consen- sus. Of the three variables analyzed, only perceived efficiency explained the local consensus on the use of medicinal plants (p < 0.002). This result indicates that perceived efficiency is the key factor deter- mining the most popular medicinal plant when requested for memory recall, regardless of the perceived availability of the plant or the perceived frequency of diseases it treats. However, looking through the evolutionary perspective, the main question is to understand whether this factor is the only determi- nant in explaining the nature of the generation of medicinal plants’ salience, or if other ’cofactors’ of the social-ecological systems act together in an important way to guide this process as well.